A Bibliometric Analysis of Publications on Systems Thinking in Chemistry Education using Vosviewer, - Kisworo, Banu; Mudzakir, Ahmad; Liliasari, Liliasari; Permanasari, Anna (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
This study utilizes a bibliometric approach along with computational mapping analysis. This study employs a bibliometric approach, complemented by computational mapping using VOSviewer, to explore systems thinking research in chemistry education. The primary goal is to identify key research themes and trends in this field. The initial step involved searching for articles with keywords like